THE SOCIO-PEDAGOGICAL NARRATIVE VASILIA GLÌBOVIC'KA IN THE DISCOURSE OF EDUCATION FOR ORPHANS IN WESTERN UKRAINE (END OF XIX – FIRST HALF OF XX CENTURY) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The article regards an issue of narrative in the socio-pedagogical sciences. The author shows the essence of social orphanhood in the personal narrative space of Vasilia Glìbovic'ka. Analyzing methods of socio-pedagogical narrative in the discourse of orphans education in Western Ukraine XIX-XX, author stresses that narrative techniques include observation of the attention processes, messages, constructing and generalization of data memory. She also emphasize the role of narrative in contemporary theological practices in the context of their impact on the consciousness of the orphans.
Keywords: socio-pedagogical narrative theology narrative, social orphans, orphanages, boarding schools, mentoring, a monastic congre- gation.